PENGARUH PENGGUNAAN ADULT EARLY WARNING SCORING (AEWS) TERHADAP TINGKAT MORTALITAS DI RSUD BALI MANDARA - Budi Ayu Mira Dewi; I Made Dwie Pradnya Susila; A.A. Kompiang Ngurah Darmawan3 (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2020)
The high mortality rate in hospital is a sign of service quality problems. Therefore, strategies are needed to reduce the death rate, one of them is by detecting the emergence of patients before worsening by applying the Early Warning Scoring System (EWSS), according to the age group. Adult Early Warning Score (AEWS) is a score monitoring tool to identify changes in the condition of adult patients (?15 years) using physiological parameters. The purpose of this study was to determine the effect of using AEWS on mortality rates. This study used a quantitative approach with one group pre-post-test design. The sampling technique was non probability sampling with a total sampling method. Data was analyzed by paired t-test. The results showed that the mortality rate before using AEWS belonged to the low category with the number of gross deaths 8.8 per 1000 inpatient visit or as many as 21 respondents, while the mortality rate after using AEWS was included in the low category with the number of crude deaths 3.2 per 1000 inpatient visit or as many as 12 respondents. The results of the bivariate analysis showed that p-value = 0.001 (p ? 0.05). These results indicated that there was an effect of using adult early warning scoring (AEWS) on mortality rates in Bali Mandara Hospital.